(untitled) (CIPEEX, 2022)
OBJECTIVE: TO ANALYZE THE INVOLVEMENT OF PHYSICAL EXERCISE IN LESSENING THE SIGNS AND SYMPTOMS OF CLIMACTERIC. METHODS: IT€™S AN INTEGRATIVE LITERATURE REVIEW THAT FOLLOWS THE PICO STRATEGY. A CAREFUL SEARCH WAS MADE IN THE DATABASES NATIONAL LIBRARY OF MEDICINE AND NATIONAL INSTITUTES OF HEALTH (PUBMED) AND BIBLIOTECA VIRTUAL EM SAÚDE (BVS), CARRIED OUT BETWEEN AUGUST AND SEPTEMBER 2022. THE DESCRIPTORS €ŒCLIMATERIC€; €ŒEXERCISE€; €ŒMENOPAUSE€; €ŒSIGNS AND SYMPTOMS€ WERE USED, AS WELL AS IT€™S RESPECTIVES TERMS IN ENGLISH. THE CAREFUL INTEGRATIVE SEARCH RESULTED IN NINETY ARTICLES. AFTER APPLYING THE ELIGIBILITY CRITERIA, SEVENTEEN PRIMARY STUDIES WERE INCLUDED. RESULTS: MOST OF THE SELECTED ARTICLES POINTED OUT THAT THE PRACTICE OF PHYSICAL EXERCISE - WHETHER AEROBIC, ANAEROBIC OR RESISTANCE - RESULTED IN SIGNIFICANCE IMPROVEMENT OF THE CARDIOVASCULAR, METABOLIC AND ENDOCRINE SYMPTOMS THAT AFFECT WOMEN DURING THE CLIMACTERIC PERIOD. FINAL CONSIDERATIONS: IT CAN BE CONCLUDED THAT THE PRACTICE OF PHYSICAL EXERCISES SHOULD BE USED AS A FORM OF TREATMENT, DUE TO ITS HIGH POTENTIAL TO ALLEVIATE SYMPTOMS PRESENT IN THE CLIMACTERIC PERIOD. HOWEVER, FURTHER STUDIES ARE NEEDED TO FILL THE DATA GAPS.